Gut-muscle crosstalk. A perspective on influence of microbes on muscle function - Chew, Weixuan; Lim, Yen Peng; Lim, Wee Shiong; Chambers, Edward S.; Frost, Gary; Wong, Sunny Hei; Ali, Yusuf (Frontiers in Medicine, 2023)
Our gastrointestinal system functions to digest and absorb ingested food, but it is also home to trillions of microbes that change across time, nutrition, lifestyle, and disease conditions. Largely commensals, these microbes are gaining prominence with regards to how they collectively affect the function of important metabolic organs, from the adipose tissues to the endocrine pancreas to the skeletal muscle. Muscle, as the biggest utilizer of ingested glucose and an important reservoir of body proteins, is intricately linked with homeostasis, and with important anabolic and catabolic functions, respectively. Herein, we provide a brief overview of how gut microbiota may influence muscle health and how various microbes may in turn be altered during certain muscle disease states. Specifically, we discuss recent experimental and clinical evidence in support for a role of gut-muscle crosstalk and include suggested underpinning molecular mechanisms that facilitate this crosstalk in health and diseased conditions. We end with a brief perspective on how exercise and pharmacological interventions may interface with the gut-muscle axis to improve muscle mass and function.